New approaches to the synthesis of anisotropic, core-shell and hollow metal nanostructures - Sastry, M.; Swami, A.; Mandal, Sujata; Selvakannan, P. R. (Journal of Materials Chemistry, 2005)
The synthesis of nanomaterials with control over size, shape and chemical composition continues to be a major challenge in nanoscience. The requirements of nanomaterial synthesis are becoming more sophisticated and, in addition to anisotropic structures, there is much excitement surrounding the development of recipes for the synthesis of core-shell and hollow nanostructures. Much of the motivation for research in this direction stems from the unusual optoelectronic and chemical properties exhibited by such nanostructures. In this article, we review the work from this laboratory on the synthesis of flat gold nanostructures at the air-water interface, either by confining the reductant or the precursor metal ions to the air-water interface. We also describe the synthesis of phase-pure core-shell nanoparticles by immobilizing UV- and pH-dependent reducing agents on the surface of the core nanoparticles as well as the synthesis of organically soluble hollow-shell nanostructures via transmetallation reactions.

Mesoporous, ligand free Cu-Fe solid catalyst mediated CS cross coupling of thiols with aryl halides - Dumbre, Deepa K.; Selvakannan, P. R.; Patil, S. K.; Choudhary, Vasant R.; Bhargava, Suresh Kumar (Applied Catalysis A-General, 2014)
Solid catalyst derived from Cu-Fe hydrotalcite was demonstrated to be a novel, ligandless, efficient and environmentally greener catalyst for the synthesis of diaryl sulfurs from the C-S cross coupling reaction of substituted thiols with different aryl halides. This catalyst has shown higher product yield in the presence of dimethylformamide (as a solvent) and K2CO3 (as a base) at 120 C. Influence of different solvents and bases on the product yield has also been investigated. The catalyst can be easily separated from the reaction mixture, simply by filtration and reused several times without a significant loss of its activity. The catalyst has been fully characterized for its surface and bulk properties and the mesoporous CuO:Fe2O3 phase was attributed for its catalytic activity towards S-arylation reactions. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: C-S cross coupling; Cu-Fe-hydrotalcite; S-arylation

Charge-switchable gold nanoparticles for enhanced enzymatic thermostability - Shankar, Shiv; Soni, Sarvesh K.; Daima, Hemant K.; Selvakannan, P. R.; Khire, Jayant Malhar; Bhargava, Suresh Kumar; Bansal, Vipul (Physical Chemistry Chemical Physics, 2015)
This study illustrates a facile strategy for efficient immobilization of enzymes on a metal nanoparticle surface. The strategy proposed here enables the enzymatic activity to be retained while increasing the enzyme thermostability. It is demonstrated that the use of a zwitterionic amino acid tyrosine as a reducing and capping agent to synthesise gold nanoparticles allows efficient immobilization of phytase enzyme through charge-switchable electrostatic interactions. The detailed kinetic and thermodynamic studies reveal that the proposed enzyme immobilization strategy improves the overall quality of phytase by reducing the activation energy required for substrate hydrolysis and broadening the temperature window in which immobilized enzyme is able to operate. The outcomes of this study indicate that the underlying zwitterionic nature of 20 natural amino acids along with significant variability in their isoelectric points and hydropathy indices as well the ability of some of the amino acids to reduce metal ions is likely to offer significant opportunities for tailoring nano-bio interfaces in a rational manner for a range of biological applications.

Green synthesis of silver nanoribbons from waste X-ray films using alkaline protease - Shankar, Shiv; Prasad, R. G. S. V.; Selvakannan, P. R.; Jaiswal, Lily; Laxman, Ryali Seeta (Materials Express, 2015)
This work illustrates a facile approach to synthesize silver nanoribbons from waste X-ray films using alkaline protease from Beauveria sp. MTCC 5184 (BAP). The green synthesized nanoribbons have been characterized by UV-Vis spectroscopy, TEM, and FTIR. The UV-visible spectra gave maximum absorbance at 400 nm. TEM micrograph showed well-dispersed silver nanoribbons with an average length of 200-400 nm. FTIR result demonstrated the respective bands of the silver nanoribbons and proteins. XRD data revealed crystalline nature of silver nanoribbons dominated with (111) facets. In vitro antibacterial activity in terms of minimum inhibitory concentrations (MIC) and minimum bactericidal concentration (MBC) showed 8/16 mu g/mL (MIC/MBC) against Staphylococcus aureus ATCC 29213 and 4/8 mu g/mL (MIC/MBC) against Escherichia coli ATCC 25922. The green synthesized silver nanoribbons showed excellent biocompatibility up to 40 mu g/mL concentrations on mouse fibroblast cell line (L929).
Keywords: Alkaline Protease; Characterization; Cytotoxicity; Silver Nanoribbons; Waste X-ray Film

Intrinsic therapeutic and biocatalytic roles of ionic liquid mediated self-assembled platinum-phytase nanospheres - Soni, Sarvesh K.; Sarkar, Sampa; Selvakannan, P. R.; Sarkar, Dhiman; Bhargava, Suresh Kumar (RSC Advances, 2015)
We herein report the inherent antitumor efficiency of self-assembled phytase enzyme nanospheres and enhance their efficiency by decorating with platinum nanoparticles and with the anticancer drug curcumin. Firstly, controlled self-assembly of phytase enzyme in an Ionic Liquid 1-butyl-3-methylimidazolium tetrafluoroborate [Bmim][BF4], led to the formation of therapeutically active phytase nanospheres. These nanospheres were further decorated with platinum nanoparticles by adding the platinum ions to these spheres and the nanoparticles formation was mediated by the specific interaction between the histidine residue (in active site of phytase enzymes) and the platinum ions and subsequent reduction of the ions into nanoparticles. The enzyme spheres act as a functional soft template for the as-formed platinum nanoparticles. These Platinum decorated hybrid biomacromolecular phytase nanospheres were loaded with the anticancer drug curcumin and all the different kinds of nanospheres were subjected to in vitro cytotoxicity for their anticancer effect on three different kinds of cancer cell lines i.e. MCF-7, Hep-G2 and THP-1 derived human macrophages. We observed a gradual increase in the anticancer effect caused by only phytase nanospheres (25%), platinum-phytase nanospheres (37%), phytase-curcumin (78%) and platinum-phytase-curcumin nanospheres (90%) that establishes this protein based system as a robust combinatorial drug delivery vehicle. The platinum-phytase spheres also proved their usability as a highly efficient green and reusable biocatalytic system for phytate degradation. The present work facilitates our understanding of ionic liquid based synthesis for multifunctional protein based drug delivery vehicles incorporating combinatorial chemotherapy for potential application as biopharmaceutical agents for tumor treatment and bio-catalysis.